Integral equation

Calculus Level 3

Find the value of a a satisfying 0 π a e tan x ( tan 3 x + tan x ) d x = 1. \int_0^{\frac{\pi}{ a}} e^{\tan x} (\tan^3 x + \tan x) \, dx = 1 .


The answer is 4.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Jan 27, 2016

0 π a e tan x ( tan 3 x + tan x ) d x = 1 0 π a e tan x tan x ( tan 2 x + 1 ) d x = 1 0 π a e tan x tan x sec 2 x d x = 1 Let t = tan x d t = sec 2 x d x 0 tan π a t e t d t = 1 By integration by parts: u = t d v = e t d t [ t e t ] 0 tan π a 0 tan π a e t d t = 1 e tan π a tan π a [ e t ] 0 tan π a = 1 e tan π a tan π a e tan π a + 1 = 1 e tan π a tan π a = e tan π a tan π a = 1 a = 4 \begin{aligned} \int_0^\frac{\pi}{a} e^{\tan x}(\tan^3 x + \tan x) \space dx & = 1 \\ \int_0^\frac{\pi}{a} e^{\tan x}\tan x(\tan^2 x + 1) \space dx & = 1 \\ \int_0^\frac{\pi}{a} e^{\tan x}\tan x \sec^2 x \space dx & = 1 \quad \quad \small \color{#3D99F6}{\text{Let } t = \tan x \quad \Rightarrow dt = \sec^2 x \space dx} \\ \Rightarrow \int_0^{\tan \frac{\pi}{a}} \color{#D61F06}t \color{#3D99F6}{e^{t} \space dt} & = 1 \quad \quad \small \color{#3D99F6}{\text{By integration by parts: } \color{#D61F06} {u = t} \quad \color{#3D99F6} dv = e^t \space dt} \\ \left[te^t\right]_0^{\tan \frac{\pi}{a}} - \int_0^{\tan \frac{\pi}{a}} e^{t} \space dt & = 1 \\ e^{\tan \frac{\pi}{a}} \tan \frac{\pi}{a}- \left[e^t\right]_0^{\tan \frac{\pi}{a}} & = 1 \\ e^{\tan \frac{\pi}{a}} \tan \frac{\pi}{a}- e^{\tan \frac{\pi}{a}} + 1 & = 1 \\ e^{\tan \frac{\pi}{a}} \tan \frac{\pi}{a} & = e^{\tan \frac{\pi}{a}} \\ \Rightarrow \tan \frac{\pi}{a} & = 1 \\ \Rightarrow a & = \boxed{4} \end{aligned}

0 π 4 e tan x ( ( tan x ) 3 + tan x ) d x = 0 π 4 e tan x tan x ( ( tan x ) 2 + 1 ) d x = \int_0^\frac{\pi}{4} e^{\tan x}((\tan x)^3 + \tan x) dx =\int_0^\frac{\pi}{4} e^{\tan x}\tan x((\tan x)^2 + 1) dx = [ e t a n x tan x ] 0 π 4 0 π 4 e tan x ( ( tan x ) 2 + 1 ) d x \left[e^{tan x} \cdot \tan x\right]^\frac{\pi}{4}_0 - \int_0^\frac{\pi}{4} e^{\tan x}((\tan x)^2 + 1) dx = e [ e tan x ] 0 π 4 = e ( e 1 ) = 1 = e - \left[e^{\tan x} \right]^\frac{\pi}{4}_0 = e - ( e - 1) =1

Question: are there more possibilities for a?

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...